The total irregularity strength of m copies of the friendship graph - Meilin Tilukay; Harmanus Batkunde (Tensor: Pure and Applied Mathematics Journal, 2022)
This paper deals with the totally irregular total labeling of the disjoin union of friendship graphs. The results shows that the disjoin union of copies of the friendship graph is a totally irregular total graph with the exact values of the total irregularity strength equals to its edge irregular total strength.